The Periodic Table : A Very Short Introduction - Scerri, Eric R. (Oxford : Oxford University Press, 2011)
The periodic table is an iconic symbol of science, and an understanding of it is essential to the physical sciences. In this volume the author presents an exploration of the periodic table in the physical sciences, considering the deeper implications of the arrangements of the table to atomic physics and quantum mechanics. He shows how this scientific knowledge about the elements was gained and considers its wider meaning. He introduces the significant figures in the development of the periodic table, as well as key ideas about early atomic theory and quantum mechanics. Also considered is the debated question of whether there is an optimal periodic table, and if so, what form it might take.
The elements -- A quick overview of the modern periodic table -- Atomic weight, triads, and Prout -- Steps toward the periodic table -- The Russian genius, Mendeleev -- Physics invades the periodic table -- Electronic structure -- Quantum mechanics -- Modern alchemy: from missing elements to synthetic elements -- Forms of the periodic table.
Includes bibliographical references (page 139) and index.
Keywords: Periodic law -- Tables; Chemical elements